2019
DOI: 10.1177/2151459319870682
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in Hip Fracture Units: Contemporary Practices in Preoperative Supplementation

Abstract: Introduction: Patients with hip fractures pose a significant burden on health services. Malnutrition, frailty, and cognitive impairment are common, and key to addressing the needs of this vulnerable patient group is nutrition optimization, including reduction in arbitrary nil by mouth (NBM) perioperative regimens. In order to understand current practices, we characterize preoperative nutrition in a regional hip fracture population. Methods: Prospective data were submitted to the National Hip Fracture Database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Nutritional status in elderly patients with fracture can deteriorate during hospital stay compounded by an increased energy expenditure and requirement, owing to post-surgical repair of traumatic hip fracture [11,12]. Studies have shown that nutritional supplements prevented weight loss in both malnourished and nourished patients and this is associated with a lower risk of postsurgical complications, shorter duration of hospital stay and a significant decrease in the 1-year mortality rate[13e15].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional status in elderly patients with fracture can deteriorate during hospital stay compounded by an increased energy expenditure and requirement, owing to post-surgical repair of traumatic hip fracture [11,12]. Studies have shown that nutritional supplements prevented weight loss in both malnourished and nourished patients and this is associated with a lower risk of postsurgical complications, shorter duration of hospital stay and a significant decrease in the 1-year mortality rate[13e15].…”
Section: Introductionmentioning
confidence: 99%
“…Estes estão associados a redução das complicações provocadas pela desnutrição e mostram redução no tempo de hospitalização em até 4 dias. 11,12 O início da suplementação oral está indicado para pacientes que apresentam redução da ingestão alimentar a valores menores que 60% do valor calórico total recomendado. Considera-se, que o grupo de maior risco de baixa ingesta oral são aqueles previamente desnutridos ou em risco nutricional a partir do diagnóstico pela triagem, ou que apresentam demanda metabólica aumentada, sarcopenia, lesão de pele, oncológicos e preparo préoperatório.…”
Section: Introductionunclassified